Effect of a punctal plug on ocular surface disease in patients using topical prostaglandin analogues: a randomized controlled trial. (24th May 2018) - Sherwin, Justin C; Ratnarajan, Gokulan; Elahi, Babar; Bilkiewicz‐Pawelec, Anna; Salmon, John F
Abstract: Importance: Ocular surface disease (OSD) is common and can reduce treatment compliance and quality of life. Background: To determine whether a punctal plug improves OSD and reduces intraocular pressure (IOP) in patients using prostaglandin analogue monotherapy. Design: Randomized controlled trial. Participants: Sixty eligible subjects aged >18 years with symptomatic OSD from glaucoma clinics were invited to participate. Lacrimal or glaucoma surgery, lid malposition and contact lens wear were exclusion criteria. Methods: One eye received an inferior punctal plug, leaving the fellow eye as a control. Main Outcome Measures: Ocular surface disease index (OSDI), tear film breakup time (TF‐BUT), Oxford cornea score, tear osmolarity and IOP were compared at baseline and 6 weeks by masked investigators. Results: From 60 eligible, 48 (80.0%) participated (mean age 69.6 years; 60.0% female). OSDI reduced following plug insertion (mean difference [MD] 14.5, 95% confidence interval [CI] 5.06–23.94, P < 0.001). Compared to control eyes, in eyes receiving plugs the TF‐BUT increased (MD 2.3 s, 95% CI 1.4–3.2, P < 0.001), the Oxford cornea score decreased (MD 0.5, 95% CI 0.3–0.7, P < 0.001), and tear osmolarity decreased (MD 10 mOsm/L, 95% CI 3.5–16.5, P = 0.003). Punctal plugs resulted in a significantly lowered IOP (MD 1.5 mmHg, 95% CI 0.1–2.9, P = 0.032). Sub‐group analyses showed similar efficacy regardless of prostaglandin preservative status or lubricant drop use. Plugs were well tolerated but extrusion occurred in 8.5%, and epiphora increased in 6.5% eyes. Conclusions and Relevance: Punctal plug insertion improves subjective and objective measures of OSD and results in a reduced IOP in patients with symptomatic ocular surface disease using prostaglandin analogue monotherapy.